Development and Characterization of Aluminium Based Matrix Using 5% Fly Ash - Singh, Karamjot; Kaushal, Gagandeep; Sidhu, Hazoor Singh (Asian Journal of Engineering and Applied Technology, 2014)
Stir casting technique is a conventional and cheap method for the fabrication of Metal Matrix Composites (MMCs). In the present research, Al-6063 as matrix material and fly ash as particulate reinforcement was fabricated with the help of stir casting technique to produce low cost AMC. In this work, the effect of height of stirring blades was investigated with variable speeds. The wt% of fly ash kept constant to 5%. To obtain the influence of these parameters on the mechanical properties of cast samples, hardness test, Charpy Impact test and SEM/EDS were performed on the cast samples.